2014
DOI: 10.2319/042814-308.1
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of cone beam computed tomography to the detection of apical root resorption after orthodontic treatment in root-filled and vital teeth

Abstract: Objective: To investigate whether root-filled teeth are similar to vital pulp teeth in terms of apical root resorption (ARR) after orthodontic treatment. Materials and Methods: An original sample of cone beam computed tomography (CBCT) images of 1256 roots from 30 orthodontic patients were analyzed. The inclusion criteria demanded rootfilled teeth and their contralateral vital teeth, while teeth with history of trauma had to be excluded to comply with exclusion criteria. CBCT images of root-filled teeth were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 25 publications
4
23
0
2
Order By: Relevance
“…Castro et al 12 conducted a study similar to the present study. In their study, 30 subjects with at least one root-filled tooth and cone-beam computed tomography (CBCT) images before and after treatment were included.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Castro et al 12 conducted a study similar to the present study. In their study, 30 subjects with at least one root-filled tooth and cone-beam computed tomography (CBCT) images before and after treatment were included.…”
Section: Discussionsupporting
confidence: 56%
“…In the literature, the results of studies investigating OIEARR in root-filled teeth are controversial. Some studies [9][10][11] reported that root-filled teeth are a risk factor for OIEARR, whereas others [12][13][14][15][16][17] concluded there is no difference in terms of OIEARR between vital and root-filled teeth. In contrast, there are also many studies [18][19][20][21][22][23][24][25] reporting less OIEARR in rootfilled teeth than in vital teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Walau bagaimanapun, kajian terhadap kesan jangka masa panjang rawatan ortodontik menunjukkan tiada perbezaan yang ketara dalam kejadian karies, penyakit periodontal atau kehilangan gigi antara individu yang mendapatkan dan tidak mendapatkan rawatan ortodontik (Thomson 2002) . Kesan rawatan ortodontik yang paling ketara adalah penyerapan akar gigi (Castro et al 2015(Castro et al , 2013Lund et al 2010). Antara penyerapan akar gigi yang paling kerap berlaku semasa rawatan ortodontik adalah jenis penyerapan akar apeks luaran (PAAL) (Topkara et al 2012).…”
Section: Pendahuluanunclassified
“…Different types of forces Paper extracted from Doctor thesis entitled "Effect of Self versus Conventionally Ligating Orthodontic Brackets on Root Surface and Bone Density" and magnitudes were compared in the literature (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) to decrease the amount of root resorption. Apical root resorption was compared (27,28) in vital versus endodontically treated teeth after orthodontic treatment. Also, the extent of external root resorption was compared in asthmatic patients versus medically free patients after fixed orthodontic treatment (29) .…”
Section: Introductionmentioning
confidence: 99%